--- layout: post title: "Typoclassopedia: Exercise solutions" date: 2017-09-27 permalink: typoclassopedia-exercise-solutions/ categories: programming math: true toc: true --- I wanted to get proficient in Haskell so I decided to follow [An [Essential] Haskell Reading List](http://www.stephendiehl.com/posts/essential_haskell.html). There I stumbled upon [Typoclassopedia](https://wiki.haskell.org/Typeclassopedia), while the material is great, I couldn't find solutions for the exercises to check against, so I decided I would write my own and hopefully the solutions would get fixed in case I have gone wrong by others. So if you think a solution is wrong, let me know in the comments! In each section below, I left some reference material for the exercises and then the solutions. Note: The post will be updated as I progress in Typoclassopedia myself Functor ========== ## Instances ```haskell instance Functor [] where fmap :: (a -> b) -> [a] -> [b] fmap _ [] = [] fmap g (x:xs) = g x : fmap g xs -- or we could just say fmap = map instance Functor Maybe where fmap :: (a -> b) -> Maybe a -> Maybe b fmap _ Nothing = Nothing fmap g (Just a) = Just (g a) ``` > ((,) e) represents a container which holds an “annotation” of type e along with the actual value it holds. It might be clearer to write it as (e,), by analogy with an operator section like (1+), but that syntax is not allowed in types (although it is allowed in expressions with the TupleSections extension enabled). However, you can certainly think of it as (e,). > ((->) e) (which can be thought of as (e ->); see above), the type of functions which take a value of type e as a parameter, is a Functor. As a container, (e -> a) represents a (possibly infinite) set of values of a, indexed by values of e. Alternatively, and more usefully, ((->) e) can be thought of as a context in which a value of type e is available to be consulted in a read-only fashion. This is also why ((->) e) is sometimes referred to as the reader monad; more on this later. ### Exercises 1. Implement `Functor` instances for `Either e` and `((->) e)`. **Solution**: ```haskell instance Functor (Either e) where fmap _ (Left e) = Left e fmap g (Right a) = Right (g a) instance Functor ((->) e) where fmap g f = g . f ``` 2. Implement `Functor` instances for `((,) e)` and for `Pair`, defined as below. Explain their similarities and differences. **Solution**: ```haskell instance Functor ((,) e) where fmap g (a, b) = (a, g b) data Pair a = Pair a a instance Functor Pair where fmap g (Pair a b) = Pair (g a) (g b) ``` Their similarity is in the fact that they both represent types of two values. Their difference is that `((,) e)` (tuples of two) can have values of different types (kind of `(,)` is `* -> *`) while both values of `Pair` have the same type `a`, so `Pair` has kind `*`. 3. Implement a `Functor` instance for the type `ITree`, defined as ```haskell data ITree a = Leaf (Int -> a) | Node [ITree a] ``` **Solution**: ```haskell instance Functor ITree where fmap g (Leaf f) = Leaf (g . f) fmap g (Node xs) = Node (fmap (fmap g) xs) ``` To test this instance, I defined a function to apply the tree to an `Int`: ```haskell applyTree :: ITree a -> Int -> [a] applyTree (Leaf g) i = [g i] applyTree (Node []) _ = [] applyTree (Node (x:xs)) i = applyTree x i ++ applyTree (Node xs) i ``` This is not a standard tree traversing algorithm, I just wanted it to be simple for testing. Now test the instance: ```haskell λ: let t = Node [Node [Leaf (+5), Leaf (+1)], Leaf (*2)] λ: applyTree t 1 [6,2,2] λ: applyTree (fmap id t) 1 [6,2,2] λ: applyTree (fmap (+10) t) 1 [16, 12, 12] ``` 4. Give an example of a type of kind `* -> *` which cannot be made an instance of `Functor` (without using `undefined`). I don't know the answer to this one yet! 6. Is this statement true or false? > The composition of two `Functor`s is also a `Functor`. If false, give a counterexample; if true, prove it by exhibiting some appropriate Haskell code. **Solution**: It's true, and can be proved by the following function: ```haskell ffmap :: (Functor f, Functor j) => (a -> b) -> f (j a) -> f (j b) ffmap g = fmap (fmap g) ``` You can test this on arbitrary compositions of `Functor`s: ```haskell main = do let result :: Maybe (Either String Int) = ffmap (+ 2) (Just . Right $ 5) print result -- (Just (Right 7)) ``` ## Functor Laws ```haskell fmap id = id fmap (g . h) = (fmap g) . (fmap h) ``` ### Exercises 1. Although it is not possible for a Functor instance to satisfy the first Functor law but not the second (excluding undefined), the reverse is possible. Give an example of a (bogus) Functor instance which satisfies the second law but not the first. **Solution**: This is easy, consider this instance: ```haskell instance Functor [] where fmap _ [] = [1] fmap g (x:xs) = g x: fmap g xs ``` Then, you can test the first and second laws: ```haskell λ: fmap id [] -- [1], breaks the first law λ: fmap ((+1) . (+2)) [1,2] -- [4, 5], second law holds λ: fmap (+1) . fmap (+2) $ [1,2] -- [4, 5] ``` 2. Which laws are violated by the evil Functor instance for list shown above: both laws, or the first law alone? Give specific counterexamples. ```haskell -- Evil Functor instance instance Functor [] where fmap :: (a -> b) -> [a] -> [b] fmap _ [] = [] fmap g (x:xs) = g x : g x : fmap g xs ``` **Solution**: The instance defined breaks the first law (`fmap id [1] -- [1,1]`), but holds for the second law. Category Theory =============== The Functor section links to [Category Theory](https://en.wikibooks.org/wiki/Haskell/Category_theory), so here I'm going to cover the exercises of that page, too. ## Introduction to categories ### Category laws: 1. The compositions of morphisms need to be **associative**: $f \circ (g \circ h) = (f \circ g) \circ h$ 2. The category needs to be **closed** under the composition operator. So if $f : B \to C$ and $g: A \to B$, then there must be some $h: A \to C$ in the category such that $h = f \circ g$. 3. Every object $A$ in a category must have an identity morphism, $id_A : A \to A$ that is an identity of composition with other morphisms. So for every morphism $g: A \to B$: $g \circ id_A = id_B \circ g = g$. ### Exercises 1. As was mentioned, any partial order $(P, \leq)$ is a category with objects as the elements of P and a morphism between elements a and b iff $a \leq b$. Which of the above laws guarantees the transitivity of $\leq$? **Solution**: The second law, which states that the category needs to be closed under the composition operator guarantess that because we have a morphism $a \leq b$, and another morphism $b \leq c$, there must also be some other morphism such that $a \leq c$. 2. If we add another morphism to the above example, as illustrated below, it fails to be a category. Why? Hint: think about associativity of the composition operation. ![not a category, an additional h: B -> A](/img/typoclassopedia/not-a-cat.png) **Solution**: The first law does not hold: $f \circ (g \circ h) = (f \circ g) \circ h$ To see that, we can evaluate each side to get an inequality: $g \circ h = id_B$ $f \circ g = id_A$ $f \circ (g \circ h) = f \circ id_B = f$ $(f \circ g) \circ h = id_A \circ h = h$ $f \neq h$ ## Functors ### Functor laws: 1. Given an identity morphism $id_A$ on an object $A$, $F(id_A)$ must be the identity morphism on $F(A)$, so: $F(id_A) = id_{F(A)}$ 2. Functors must distribute over morphism composition: $F(f \circ g) = F(f) \circ F(g)$ ### Exercises 1. Check the functor laws for the diagram below. ![functor diagram](/img/typoclassopedia/functor-diagram.png) **Solution**: The first law is obvious as it's directly written, the pale blue dotted arrows from $id_C$ to $F(id_C) = id_{F(C)}$ and $id_A$ and $id_B$ to $F(id_A) = F(id_B) = id_{F(A)} = id_{F(B)}$ show this. The second law also holds, the only compositions in category $C$ are between $f$ and identities, and $g$ and identities, there is no composition between $f$ and $g$. (Note: The second law always hold as long as the first one does, as was seen in Typoclassopedia) 2. Check the laws for the Maybe and List functors. **Solution**: ```haskell instance Functor [] where fmap :: (a -> b) -> [a] -> [b] fmap _ [] = [] fmap g (x:xs) = g x : fmap g xs -- check the first law for each part: fmap id [] = [] fmap id (x:xs) = id x : fmap id xs = x : fmap id xs -- the first law holds recursively -- check the second law for each part: fmap (f . g) [] = [] fmap (f . g) (x:xs) = (f . g) x : fmap (f . g) xs = f (g x) : fmap (f . g) xs fmap f (fmap g (x:xs)) = fmap f (g x : fmap g xs) = f (g x) : fmap (f . g) xs ``` ```haskell instance Functor Maybe where fmap :: (a -> b) -> Maybe a -> Maybe b fmap _ Nothing = Nothing fmap g (Just a) = Just (g a) -- check the first law for each part: fmap id Nothing = Nothing fmap id (Just a) = Just (id a) = Just a -- check the second law for each part: fmap (f . g) Nothing = Nothing fmap (f . g) (Just x) = Just ((f . g) x) = Just (f (g x)) fmap f (fmap g (Just x)) = Just (f (g x)) = Just ((f . g) x) ``` Applicative =========== ## Laws 1. The identity law: ```haskell pure id <*> v = v ``` 2. Homomorphism: ```haskell pure f <*> pure x = pure (f x) ``` Intuitively, applying a non-effectful function to a non-effectful argument in an effectful context is the same as just applying the function to the argument and then injecting the result into the context with pure. 3. Interchange: ```haskell u <*> pure y = pure ($ y) <*> u ``` Intuitively, this says that when evaluating the application of an effectful function to a pure argument, the order in which we evaluate the function and its argument doesn't matter. 4. Composition: ```haskell u <*> (v <*> w) = pure (.) <*> u <*> v <*> w ``` This one is the trickiest law to gain intuition for. In some sense it is expressing a sort of associativity property of (`<*>`). The reader may wish to simply convince themselves that this law is type-correct. ### Exercises (Tricky) One might imagine a variant of the interchange law that says something about applying a pure function to an effectful argument. Using the above laws, prove that ```haskell pure f <*> x = pure (flip ($)) <*> x <*> pure f ``` **Solution**: ```haskell pure (flip ($)) <*> x <*> pure f = (pure (flip ($)) <*> x) <*> pure f -- <*> is left-associative = pure ($ f) <*> (pure (flip ($)) <*> x) -- interchange = pure (.) <*> pure ($ f) <*> pure (flip ($)) <*> x -- composition = pure (($ f) . (flip ($))) <*> x -- homomorphism = pure ((flip ($) f) . (flip ($))) <*> x -- identical = pure f <*> x ``` Explanation of the last transformation: `flip ($)` has type `a -> (a -> c) -> c`, intuitively, it first takes an argument of type `a`, then a function that accepts that argument, and in the end it calls the function with the first argument. So `(flip ($) 5)` takes as argument a function which gets called with `5` as it's argument. If we pass `(+ 2)` to `(flip ($) 5)`, we get `(flip ($) 5) (+2)` which is equivalent to the expression `(+2) $ 5`, evaluating to `7`. `flip ($) f` is equivalent to `\x -> x $ f`, that means, it takes as input a function and calls it with the function `f` as argument. The composition of these functions works like this: First `flip ($)` takes `x` as it's first argument, and returns a function `(flip ($) x)`, this function is awaiting a function as it's last argument, which will be called with `x` as it's argument. Now this function `(flip ($) x)` is passed to `flip ($) f`, or to write it's equivalent `(\x -> x $ f) (flip ($) x)`, this results in the expression `(flip ($) x) f`, which is equivalent to `f $ x`. You can check the type of `(flip ($) f) . (flip ($))` is something like this (depending on your function `f`): ```haskell λ: let f = sqrt λ: :t (flip ($) f) . (flip ($)) (flip ($) f) . (flip ($)) :: Floating c => c -> c ``` Also see [this question on Stack Overflow](https://stackoverflow.com/questions/46503793/applicative-prove-pure-f-x-pure-flip-x-pure-f/46505868#46505868) which includes alternative proofs. ## Instances Applicative instance of lists as a collection of values: ```haskell newtype ZipList a = ZipList { getZipList :: [a] } instance Applicative ZipList where pure :: a -> ZipList a pure = undefined -- exercise (<*>) :: ZipList (a -> b) -> ZipList a -> ZipList b (ZipList gs) <*> (ZipList xs) = ZipList (zipWith ($) gs xs) ``` Applicative instance of lists as a non-deterministic computation context: ```haskell instance Applicative [] where pure :: a -> [a] pure x = [x] (<*>) :: [a -> b] -> [a] -> [b] gs <*> xs = [ g x | g <- gs, x <- xs ] ``` ### Exercises 1. Implement an instance of `Applicative` for `Maybe`. **Solution**: ```haskell instance Applicative (Maybe a) where pure :: a -> Maybe a pure x = Just x (<*>) :: Maybe (a -> b) -> Maybe a -> Maybe b _ <*> Nothing = Nothing Nothing <*> _ = Nothing (Just f) <*> (Just x) = Just (f x) ``` 2. Determine the correct definition of `pure` for the `ZipList` instance of `Applicative`—there is only one implementation that satisfies the law relating `pure` and `(<*>)`. **Solution**: ```haskell newtype ZipList a = ZipList { getZipList :: [a] } instance Functor ZipList where fmap f (ZipList list) = ZipList { getZipList = fmap f list } instance Applicative ZipList where pure = ZipList . pure (ZipList gs) <*> (ZipList xs) = ZipList (zipWith ($) gs xs) ``` You can check the Applicative laws for this implementation. ## Utility functions ### Exercises 1. Implement a function `sequenceAL :: Applicative f => [f a] -> f [a]` There is a generalized version of this, `sequenceA`, which works for any `Traversable` (see the later section on `Traversable`), but implementing this version specialized to lists is a good exercise. **Solution**: ```haskell createList = replicate 1 sequenceAL :: Applicative f => [f a] -> f [a] sequenceAL = foldr (\x b -> ((++) . createList <$> x) <*> b) (pure []) ``` Explanation: First, `createList` is a simple function for creating a list of a single element, e.g. `createList 2 == [2]`. Now let's take `sequenceAL` apart, first, it does a fold over the list `[f a]`, and `b` is initialized to `pure []`, which results in `f [a]` as required by the function's output. Inside the function, `createList <$> x` applies `createList` to the value inside `f a`, resulting in `f [a]`, and then `(++)` is applied to the value again, so it becomes `f ((++) [a])`, now we can apply the function `(++) [a]` to `b` by `((++) . createList <$> x) <*> b`, which results in `f ([a] ++ b)`. ## Alternative formulation ### Definition ```haskell class Functor f => Monoidal f where unit :: f () (**) :: f a -> f b -> f (a,b) ``` ### Laws: 1. Left identity ```haskell unit ** v ≅ v ``` 2. Right identity ```haskell u ** unit ≅ u ``` 3. Associativity ```haskell u ** (v ** w) ≅ (u ** v) ** w ``` 4. Neutrality ```haskell fmap (g *** h) (u ** v) = fmap g u ** fmap h v ``` ### Isomorphism In the laws above, `≅` refers to isomorphism rather than equality. In particular we consider: ```haskell (x,()) ≅ x ≅ ((),x) ((x,y),z) ≅ (x,(y,z)) ``` ### Exercises 1. Implement `pure` and `<*>` in terms of `unit` and `**`, and vice versa. ```haskell unit :: f () unit = pure () (**) :: f a -> f b -> f (a, b) a ** b = fmap (,) a <*> b pure :: a -> f a pure x = unit ** x (<*>) :: f (a -> b) -> f a -> f b f <*> a = fmap (uncurry ($)) (f ** a) = fmap (\(f, a) -> f a) (f ** a) ``` 2. Are there any `Applicative` instances for which there are also functions `f () -> ()` and `f (a,b) -> (f a, f b)`, satisfying some "reasonable" laws? The [`Arrow`](https://wiki.haskell.org/Typeclassopedia#Arrow) type class seems to satisfy these criteria. ```haskell first unit = () (id *** f) (a, b) = (f a, f b) ``` 3. (Tricky) Prove that given your implementations from the first exercise, the usual Applicative laws and the Monoidal laws stated above are equivalent. 1. Identity Law ```haskell pure id <*> v = fmap (uncurry ($)) ((unit ** id) ** v) = fmap (uncurry ($)) (id ** v) = fmap id v = v ``` 2. Homomorphism ```haskell pure f <*> pure x = (unit ** f) <*> (unit ** x) = fmap (\(f, a) -> f a) (unit ** f) (unit ** x) = fmap (\(f, a) -> f a) (f ** x) = fmap f x = pure (f x) ``` 3. Interchange ```haskell u <*> pure y = fmap (uncurry ($)) (u ** (unit ** y)) = fmap (uncurry ($)) (u ** y) = fmap (u $) y = fmap ($ y) u = pure ($ y) <*> u ``` 4. Composition ```haskell u <*> (v <*> w) = fmap (uncurry ($)) (u ** (fmap (uncurry ($)) (v ** w))) = fmap (uncurry ($)) (u ** (fmap v w)) = fmap u (fmap v w) = fmap (u . v) w = pure (.) <*> u <*> v <*> w = ``` Monad ===== ## Definition ```haskell class Applicative m => Monad m where return :: a -> m a (>>=) :: m a -> (a -> m b) -> m b (>>) :: m a -> m b -> m b m >> n = m >>= \_ -> n fail :: String -> m a ``` ## Instances ```haskell instance Monad Maybe where return :: a -> Maybe a return = Just (>>=) :: Maybe a -> (a -> Maybe b) -> Maybe b (Just x) >>= g = g x Nothing >>= _ = Nothing ``` ### Exercises 1. Implement a `Monad` instance for the list constructor, `[]`. Follow the types! **Solution**: ```haskell instance Monad [] where return a = [a] [] >> _ = [] (x:xs) >>= f = f x : xs >>= f ``` 2. Implement a `Monad` instance for `((->) e)`. **Solution**: ```haskell instance Monad ((->) e) where return x = const x g >>= f = f . g ``` 3. Implement `Functor` and `Monad` instance for `Free f`, defined as: ```haskell data Free f a = Var a | Node (f (Free f a)) ``` You may assume that `f` has a `Functor` instance. This is known as the _free monad_ built from the functor f. **Solution**: ```haskell instance Functor (Free f) where fmap f (Var a) = Var (f a) fmap f (Node x) = Node (f x) instance Monad (Free f) where return x = Var x (Var x) >>= f = Var (f x) (Node x) >>= f = Node (fmap f x) ``` ## Intuition ### Exercises 1. Implement `(>>=)` in terms of `fmap` (or `liftM`) and `join`. **Solution**: ```haskell a >>= f = join (fmap f a) ``` 2. Now implement `join` and `fmap` (`liftM`) in terms of `(>>=)` and `return`. **Solution**: ```haskell fmap f a = a >>= (return . f) join m = m >>= id ``` ## Laws Standard: ```haskell return a >>= k = k a m >>= return = m m >>= (\x -> k x >>= h) = (m >>= k) >>= h ``` In terms of `>=>`: ```haskell return >=> g = g g >=> return = g (g >=> h) >=> k = g >=> (h >=> k) ``` ### Exercises 1. Given the definition `g >=> h = \x -> g x >>= h`, prove the equivalence of the above laws and the standard monad laws. **Solution**: ```haskell return >=> g = \x -> return x >>= g = \x -> g x = g g >=> return = \x -> g x >>= return = \x -> g x = g g >=> (h >=> k) = \y -> g y >>= (\x -> h x >>= k) = \y -> (g y >>= h) >>= k = \y -> (\x -> g x >>= h) y >>= k = (\x -> g x >>= h) >=> k = (g >=> h) >=> k ```